Regulation of postprandial mesenteric blood flow in humans: evidence for a cholinergic nervous reflex. Issue 4 (April 1991) - Sieber, C; Beglinger, C; Jaeger, K; Hildebrand, P; Stalder, G A
Abstract : Duplex ultrasound was used to investigate superior mesenteric artery haemodynamics in humans in order to determine the physiological importance of postprandial blood concentrations of cholecystokinin octapeptide (CCK8), gastrin 17, secretin, and glucagon and to study whether a nervous cholinergic reflex mechanism has a role in the postprandial mesenteric blood flow response. Duplex parameters of vessel diameter, mean velocity, and flow volume were determined serially in the basal state and after stimulation. Changes were compared with baseline values. Superior mesenteric artery parameters were significantly increased over baseline values after a liquid test meal, but ingestion of saline did not cause any changes. Hormones infused simultaneously at postprandial concentrations did not change mesenteric blood flow. When they were infused at pharmacological doses, however, a significant increase in flow parameters was observed. Pretreatment with atropine significantly (p less than 0.05) reduced the mesenteric blood flow response to meal stimulation (57%). These data suggest that the four hormones tested are not of quantitative importance in regulating postprandial superior mesenteric artery blood flow. A cholinergic nervous reflex, however, participates in the control of food induced mesenteric artery flow changes.